OC-004 Prediction of Clinical and Endoscopic Remission after Autologous Stem cell Transplantation in Treatment Refractory Crohn's Disease: Pooled Results from the Astic Trial. (17th August 2016) - Lindsay, JO; Allez, M; Clark, M; Labopin, M; Ricart, E; Satsangi, J; Rogler, G; Rovira, M; Farge, D; Hawkey, C; ,
Abstract : Introduction: The randomised controlled ASTIC trial compared autologous stem cell transplantation (HSCT) with conventional care in treatment refractory Crohn's disease (CD). Although the trial failed its ambitious primary endpoint (clinical remission for >3 months off all CD medication with no ulceration on imaging / endoscopy at 1 year) significant benefit was seen in individual components. Patients randomised to conventional care subsequently underwent HSCT. We report outcome for all patients 1 year after HSCT and identify factors that predict remission. Methods: Patients with active CD who were refrctory biologics underwent cyclophosphamide mobilisation and were randomised to immediate (4 weeks) or delayed (52 weeks) HSCT. Clinical (CDAI), endoscopic (SES-CD), and quality of life scores were compared immediately prior to (baseline) and one year after HSCT. An adjudication panel blinded to allocation and visit reviewed radiology and endoscopy. Results: 45 patients with successful mobilisation were randomised to early (n = 23) or delayed (n = 22) HSCT. Data from baseline and 1 year after HSCT were available for 40 patients. Compared to baseline, there were significant improvements at 1 year for CDAI, PRO2, quality of life (IBDQ, and EQ5D) and SES CD (see Table). Complete endoscopic regression (SES-CD score of 0 in all segments examined) occurred in 26%, with complete ulcer healing in 50% and partial healing (ulcers ≤5 mm in no more than 2 segments) in 82%. Clinical remission (CDAI < 150) at one year occurred in 46% patients (39% in remission >3 months off steroids). On univariate analysis baseline factors associated with steroid free clinical remission at 1 year include colonic localization (p = 0.006), inflammatory phenotype (p = 0.009), high SES-CD (p = 0.005). Age, CRP and early vs delayed HSCT were not significant. On multivariate analysis high baseline SES CD was associated with steroid free remission at year 1 (OR 1.21 95%CI 1.03–1.41; p = 0.017). Conclusion: One year outcome in the largest reported cohort of patients undergoing HSCT for refractory Crohn's disease shows a significant reduction in both clinical and endoscopic disease activity with an improvement in quality of life. Endoscopic severity at baseline predict outcome. Disclosure of Interest: None Declared